RANTAI PASOKAN DAN NILAI TAMBAH EDAMAME GORENG VAKUM DI UD. RAJA KERIPIK KABUPATEN JEMBER - nur afina aninnas; Ati Kusmiati; Triana Dewi Hapsari (University of Jember, 2018)
The success of the supply chain of vacuum fried green soybean can be seen from the supply chain flow of the raw materials and the continuity of the resulting product. Agro-industry activities that convert primary products into new processed products with higher economic value can provide higher added value and greater benefits when compared without going through the processing. The research aim to know: (1) product flow, finance flow, and information flow; (2) marketing margin of the supply chain; and value added of vacuum fried green soybeans in UD. Raja Keripik, Jember. The research was conducted in UD. Raja Keripik, Jember. Purposive method was used to determine the research location. Snawball technique was used as sampling technique based on information of UD Raja Keripik’s owner. The first aim was answered with descripton method, the second aim was answered by margin formula, and the last aim was answered by the analysis of Hayami value added. The result proves that (1) there are three flows in the supply chain of the vacuum fried green soybeans such as product flow, finance flow, and information flow (2) The margin distribution of marketing in supply chain shows that profit in each link is not equally. It can proved by the value of provit that are 51.90%; 6.78%; and 38.79%. (3) The value added of processing of one kilogram of vacuum fried green soybeans is Rp. 18.619,49